1999
DOI: 10.1002/(sici)1098-2744(199902)24:2<90::aid-mc3>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

A specific CpG methylation pattern of theMGMT promoter region associated with reduced MGMT expression in primary colorectal cancers

Abstract: The enzyme O6-methylguanine-DNA methyltransferase (MGMT) protects cells from the cytotoxic and mutagenic effects of alkylating agents. Approximately 20% of tumor cell lines lack MGMT activity and are highly sensitive to alkylating agents. In established cancer cell lines, MGMT expression appears to be correlated with methylation of residues in both the promoter and the body of the gene. The effect of methylation of the MGMT promoter on gene expression and carcinogenesis in primary tumors is unknown. We investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…This profile, thanks to the popularization of bisulfite-PCR techniques (Fraga and Esteller, 2002), has been expanded in additional reports of MGMT inactivation in other tumor types (Toyooka et al, 2001;Virmani et al, 2001;Choy et al, 2002;Lee et al, 2002;Maruyama et al, 2002;Smith-Sorensen et al, 2002), summarized in Figure 3. This aberrant MGMT methylation has been correlated with the loss of MGMT protein (Esteller et al, 1999a(Esteller et al, , 2002cHerfarth et al, 1999. ), lack of mRNA expression (Esteller et al, 2000a;Yin et al, 2003) and loss of enzymatic activity (Herfarth et al, 1999).…”
Section: Mgmt Protein Expression Analysis Retention Lossmentioning
confidence: 60%
“…This profile, thanks to the popularization of bisulfite-PCR techniques (Fraga and Esteller, 2002), has been expanded in additional reports of MGMT inactivation in other tumor types (Toyooka et al, 2001;Virmani et al, 2001;Choy et al, 2002;Lee et al, 2002;Maruyama et al, 2002;Smith-Sorensen et al, 2002), summarized in Figure 3. This aberrant MGMT methylation has been correlated with the loss of MGMT protein (Esteller et al, 1999a(Esteller et al, , 2002cHerfarth et al, 1999. ), lack of mRNA expression (Esteller et al, 2000a;Yin et al, 2003) and loss of enzymatic activity (Herfarth et al, 1999).…”
Section: Mgmt Protein Expression Analysis Retention Lossmentioning
confidence: 60%
“…Promoter hypermethylation and reduced MGMT expression has been found in some primary human carcinomas. [7][8][9] Data have also indicated that wild-type p53 may negatively regulate basal MGMT promoter activity. in vitro and in vivo studies have shown that induction of MGMT in the presence of DNAdamaging agents involves p53.…”
Section: Abstract: Dna Methylation Gastric Carcinoma Mgmtmentioning
confidence: 99%
“…Aberrant DNA hypermethylation at the promoter region DNA repair gene contributes to the progression of some cancers (Herfarth et al, 1999;Wu et al, 2008;Hibi et al, 2009;Sharma et al, 2009). We used MSP (Methylation-Specific PCR) to evaluate the status of the promoter methylation of MGMT gene in the different grades of meningioma tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that MGMT hypermethylation occurs in many tumor types, including gliomas, large B-cell lymphomas, retinoblastomas, and cancers of the breast, lung, prostate, stomach, and colon (Herfarth et al, 1999;Wu et al, 2008;Hibi et al, 2009;Sharma et al, 2009). Many studies have observed a high frequency of MGMT methylation in tumors, but there are only a few studies on the status of MGMT methylation in meningiomas.…”
Section: Introductionmentioning
confidence: 99%